SIMBOLISASI PENDIDIKAN RELIGIUSITAS DALAM UPACARA AGAMA ISLAM DAN KATOLIK - A Singgih Basuki (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
Art in the religious point of view is as a symbols of human in which expressive and constructive based on their believe. In Islam and Catholic the symbol itself is abstract that fit to sociocultural and reflecting their believe. More over in constructing expressive symbols will make them more concern on their believe. The existance of art in Islam and Catholic is such an unity among religious experience and art itself. An expression of art in Islam is a fitrah (gift) for human as a media in linking to Allah, but in Christian art is such praise and gratitude.